2022
DOI: 10.3847/psj/ac4eee
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Photochemical Modeling of Saturn’s Ionization Balance Including Grain Charging

Abstract: We present a semianalytical photochemical model of Saturn’s near-equatorial ionosphere and adapt it to two regions (∼2200 and ∼1700 km above the 1 bar level) probed during the inbound portion of Cassini’s orbit 292 (2017 September 9). The model uses as input the measured concentrations of molecular hydrogen, hydrogen ion species, and free electrons, as well as the measured electron temperature. The output includes upper limits, or constraints, on the mixing ratios of two families of molecules, on ion concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…This modeldata mismatch suggests that the ring vapor could not have not penetrated very far into the stratosphere by the end of the Cassini mission, or CIRS would have seen evidence for the oxygen-bearing species and HCN and HC 3 N, if not additional nitrogen species and hydrocarbon perturbations. On the other hand, the INMS measurements produce clear signals of heavy molecules in Saturn's thermosphere that do not appear to be an instrumental artifact (Waite et al, 2018;Miller et al, 2020;Serigano et al, 2022), and the INMS-inferred ring vapor influx rates are consistent to first order with ion and electron densities inferred for the ionosphere (e.g., see the models above and section 5.1, as well as Moore et al, 2018;Cravens et al, 2019;Persoon et al, 2019;Hadid et al, 2019;Morooka et al, 2019;Dreyer et al, 2021;Vigren et al, 2022). One possibility that could potentially reconcile the stratospheric results with the thermospheric results is if the inferred ring vapor during the Grand Finale were the result of a recent disruptive event in the rings that generated a recent, transient inflow of dust and vapor.…”
Section: Time-variable Modelsupporting
confidence: 56%
See 4 more Smart Citations
“…This modeldata mismatch suggests that the ring vapor could not have not penetrated very far into the stratosphere by the end of the Cassini mission, or CIRS would have seen evidence for the oxygen-bearing species and HCN and HC 3 N, if not additional nitrogen species and hydrocarbon perturbations. On the other hand, the INMS measurements produce clear signals of heavy molecules in Saturn's thermosphere that do not appear to be an instrumental artifact (Waite et al, 2018;Miller et al, 2020;Serigano et al, 2022), and the INMS-inferred ring vapor influx rates are consistent to first order with ion and electron densities inferred for the ionosphere (e.g., see the models above and section 5.1, as well as Moore et al, 2018;Cravens et al, 2019;Persoon et al, 2019;Hadid et al, 2019;Morooka et al, 2019;Dreyer et al, 2021;Vigren et al, 2022). One possibility that could potentially reconcile the stratospheric results with the thermospheric results is if the inferred ring vapor during the Grand Finale were the result of a recent disruptive event in the rings that generated a recent, transient inflow of dust and vapor.…”
Section: Time-variable Modelsupporting
confidence: 56%
“…The dominance of HCNH + at the main peak in our Case A model is consistent with the combined INMS and RPWS data analysis that points to a heavy ion being the dominant species at the main peak (Cravens et al, 2019); it also satisfies the combined RPWS/LP and INMS analysis that suggests that the main-peak ion should have a recombination rate coefficient ≲3 × 10 −7 cm 3 s −1 if the ion densities inferred by Morooka et al (2019) are correct (Dreyer et al, 2021) (but see Johansson et al 2022 for an alternate interpretation). However, the H + /H 3 + ratio predicted by the model at 3 × 10 −7 mbar, the deepest point in the trajectory of orbit 292, is much smaller than is observed (Waite et al, 2018;Moore et al, 2018), and the observed ion and electron densities at this pressure level are inconsistent with the INMS-inferred abundance of neutral species that are able to react with H + and maintain photochemical equilibrium (Vigren et al, 2022). These issues are not limited to Case A and are discussed more completely in section 5.1.…”
Section: Case a Ion Chemistrymentioning
confidence: 66%
See 3 more Smart Citations